Fiscal Risk Management of Indonesia's Tax Incentive Regime Under Global Minimum Tax: Evidence from BKPM LKPM Investment Data 2010–2026 - Mohamad Marulli (Pasca Sarjana UKI, 2026)
This study examines the fiscal risk implications of Indonesia's tax incentive regime under the OECD/G20 Pillar Two global minimum tax (GMT) framework. Indonesia's Minister of Finance Regulation No. 136 of 2024 (PMK 136/2024), effective 1 January 2025, establishes the GloBE framework including QDMTT, IIR, and UTPR, while Director General of Taxes Regulation PER-06/PJ/2026 (May 2026) governs GMT technical compliance. Using qualitative doctrinal-policy analysis combined with quantitative examination of BKPM LKPM investment realisation microdata spanning 2010 to Q1 2026 — encompassing over 700,000 records from 66 quarterly datasets — this study identifies that Indonesia's traditional profit-based incentives generate material fiscal risk under Pillar Two, as incentives reducing the effective tax rate below 15% now trigger top-up tax liabilities rather than investment benefits. Plant-level evidence from 224 foreign-owned plants confirms that Indonesia's incentives are allocated indiscriminately with respect to investor motive. The study proposes a three-phase fiscal risk mitigation framework centred on Qualified Refundable Tax Credits structured as input R&D tax credits aligned with Substance-Based Income Exclusion mechanics and GloBE compatibility requirements.